Death of a showman - Fredericks, Mariah (Fredericks, Mariah. Jane Prescott novel, 2021)
"In Mariah Fredericks's Death of a Showman, the fourth in this absorbing series set in Gilded Age New York, lady's maid Jane Prescott is thrust into the world of show business, where a killer is stalking Broadway. It's the summer of 1914 and Jane Prescott-lady's maid to Louise Tyler, daughter of a wealthy New York society family-has just arrived home from Independence Day celebrations to find musician Leo Hirschfeld playing the Tylers' piano. Jane's brief courtship with Leo had ended before the Tylers' vacation to Europe earlier in the summer, so she isn't entirely surprised to see him. She is, however, shocked to learn that he's been engaged to write a new Broadway show-and that he's married a chorus girl in his musical. Jane and Louise Tyler are pulled into the sparkling and dramatic world of Broadway, with Louise becoming an investor in the show, and Jane accompanying her to rehearsals as her chaperone. But behind the glittering facade of costumes and love songs, the cast is restless and prone to deception, culminating in the death of the show's producer: Sidney Warburton. The accusation that Leo was involved jolts Jane, and her old friend and tabloid reporter Michael Behan, into action. Determined to close the curtain on these murders, Jane must strip back the masks of these consummate actors until she knows the truth"--